PROBLEMS OF TEACHING COMPUTER DESIGN TO APPLIED DECORATIVE ARTS SPECIALISTS (Web of Teachers: Inderscience Research, 2024)
The article talks about the problems of teaching computer design to experts of applied decorative arts. Based on the role of traditional hand drawing in the process of artistic design, the author revealed the importance of design-graphic work before the object is depicted on the computer. Special integrated methods of professional training of students and methods of teaching design and applied decorative arts are also offered.